Understanding the difference between the nano and micro bubble size distributions generated by a regenerative turbine microbubble generator using ozone - John, Alexander; Brookes, Adam; Carra, Irene; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2025)
There is a genuine paucity of data concerning the relative significance of the nano and the microbubble size distributions that are collectively generated when operating microbubble generation devices. Accordingly, the current work aimed to address this knowledge gap by measuring the two size distributions generated by a regenerative turbine microbubble generator using ozone and assess the relative significance of the nanobubble fraction. The microbubble fraction was measured with a focus-beam reflectance measurement device and the nanobubble fraction with a nano particle tracking instrument. The latter was calibrated using latex spheres to understand method uncertainty and to optimise the measurement approach. Sauter mean diameters of 217 nm and 37 μm were reported for the nano and microbubble fractions, respectively, with half of the microbubbles being <5000 nm in size. A comparison of the size and number concentrations of the different bubble types revealed that the majority of the gas was contained within the microbubble fraction, and hence, this controlled the overall mass transfer performance of the system. Further, the nanobubbles were observed to be stable for 18 h with little change in their size or number, indicating there was no net transfer of their gaseous contents. Overall, the work revealed that when considering enhancing gas-liquid mass transfer processes with micro-nano bubble generators, the microbubble fraction is key.
Keywords: 4004 Chemical Engineering; 4005 Civil Engineering; 40 Engineering; 4011 Environmental Engineering; 4004 Chemical engineering; 4005 Civil engineering; 4011 Environmental engineering